STRESS-STRAIN STATE OF THE MAIN STRUCTURES OF THE BRIDGE CONVEYORS - Barbas, Yo. H.; Boyko, P. P. (Science and Transport Progress, 2010)
The review of metal designs of bridge faucets-unloaders is offered.